Cigarette smoking and steroid hormones in women. - Key, T; Pike, M; Baron, J; Moore, J; Wang, D; Thomas, B; Bulbrook, R (1991)
Epidemiological evidence has suggested that cigarette smoking has an anti-oestrogenic effect in women, but the effects of smoking on steroid hormone metabolism are not fully understood. We compared serum concentrations of oestradiol, progesterone (luteal phase) and dehydroepiandrosterone sulphate (DHEA-S), and urinary excretion rates of six steroids of predominantly adrenal origin, in healthy premenopausal and postmenopausal female smokers and non-smokers. Serum concentrations of oestradiol, progesterone and DHEA-S did not differ between smokers and non-smokers by greater than 5%, and none of these differences was statistically significant. Mean urinary excretion rates of androsterone, aetiocholanolone, DHEA, 11-keto-aetiocholanolone, 11-hydroxyandrosterone and 11-hydroxyaetiocholanolone were very similar in smokers and non-smokers in premenopausal women, but were from 2-44% higher in smokers than non-smokers in postmenopausal women. The difference was statistically significant only for 11-hydroxyandrosterone. These results confirm previous reports that cigarette smoking does not affect serum oestradiol in premenopausal or postmenopausal women, but provide only weak evidence to support previous findings of increased levels of some adrenal steroids in postmenopausal women smokers. The mechanism for the apparent anti-oestrogenic effect of cigarette smoking remains unclear.